Doctors' knowledge level and attitudes concerning avian influenza - (:unkn) unknown (My University, 2008)
Objective: Avian influenza cases have been detected in Turkey and human deaths have been reported. The aim of this study was to investigate the knowledge, attitudes, and behaviour of doctors concerning avian influenza. Method: A questionnaire was applied to a total of 172 doctors, 82 in the university, 46 in the state hospital and 44 in primary care clinics, in a district of Istanbul, in 2006. Results: The participant doctors were general practitioners(GPs) (27%), specialists(31%), and residents(42%). The male/female ratio was 48/52% and the median age value was 32(23-53). The mean knowledge score was 14.4±4.4; 15.9% of the doctors had low, 77% medium, 7% high knowledge level. Transmission (94%), symptoms in humans (94%) and preventive measures (89%) were well-known. The agent of avian flu, timing of the treatment, antiviral agents were less well-known. The GPs were more knowledgeable and felt more competent than the specialists and residents to give counselling; 53% felt competent and 74% responsible to give counselling. Half of the participants revealed a decrease in their habit of eating egg and chicken. Conclusion: Doctors need more information to enable early diagnosis and an early start to the therapy which would help to decrease fatality and to prevent the spread of the virus.
Keywords: Attitude; Avian influenza; Knowledge level